Delivery Time of Automated External Defibrillators at Apartment Houses - Uhm, Tai-Hwan; Kim, Jee-Hee (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: This study aimed to present installation criteria and a management proposal for public access defibrillation by investigating the current status of automated external defibrillators positioned in apartment housing complexes. Methods/Statistical analysis: A correlation was expected between the distance to the installed unit and the number of housing units and AEDs. Regression analysis was conducted to identify the correlations. Delivery time was determined by converting the physical distance measured by a software application (app) to the pace of a briskly walking adult. Movement time between the different levels of the apartment building was determined using a standard-speed elevator. Findings: Regression analysis revealed an intercept of 274.190 and slope of 0.106, each of which was statistically significant (p < 0.001). The regression equation was determined to be Y=274.190+0.106X. The number of housing units was equal to 274.190+0.106×180(seconds)=293, indicating that one AED for every 293 units should be the installation criterion required to enable an AED delivery of less than three minutes. Improvements/Applications: The findings of this study may be used in efforts to produce installation criteria for other public multi-use locations.